Effective Protection of the Marine Environment and Equitable Benefit Sharing in the Area: Empty Promises or Feasible Goals?. (1st May 2020) - Willaert, Klaas
Abstract: The international legal framework with regard to "the Area, " comprising the deep seabed and the subsoil beyond the boundaries of national jurisdiction, has been modified significantly through the years. It was first established by part XI of the United Nations Convention on the Law of the Sea, but the 1994 Implementation Agreement introduced several changes. These general rules and principles are further developed in the "Mining Code, " referring to the comprehensive set of regulations and procedures issued by the International Seabed Authority. The Authority has already produced rules for the first phases of mining activities (prospecting and exploration) in the Area, but has yet to adopt exploitation regulations. Nevertheless, the most recent draft of the exploitation regulations provides a good indication of the current state of play. This article analyzes the current draft of the exploitation regulations, which will shape the future deep seabed mining regime, in order to evaluate whether the relevant provisions are sufficient and effective to attain two prominent goals with regard to the Area: the protection of the marine environment and the equitable sharing of financial and economic benefits. The Law of the Sea Convention indeed states that the resources of the deep seabed are considered common heritage of mankind and prioritizes these objectives. Therefore, the exploitation regulations should strike an appropriate balance between commercial exploitation, environmental protection, and the interests of developing countries. The strengths and weaknesses of this document and the overarching international legal framework are identified and possible corrections are suggested.